Determinants of self-protection practices in online shopping among the students of higher education institutions, Malaysia - Daud, Nurul Atikaf; Muhammad Arif, Afida Mastura; Abu Bakar, Elistina; Osman, Syuhaily (Malaysian Consumer and Family Economics Association, 2020)
To date, technology has revolutionised consumer shopping experience, whereas the high internet penetration rate recorded in Malaysia causes the local online shopping market landscape to grow rapidly in recent years. Despite the convenience offered by online shopping, it also brings a new emerging area for consumer complaints and complicated issues implicating consumer protection. Accordingly, this study aimed to investigate the selfprotection practices embraced when online shopping among the students of higher education institutions in Malaysia. The data were collected through a self-administered questionnaire distributed among 400 respondents, following which a statistical analysis was performed inclusive of Pearson’s correlation and multiple linear regression. The outcome revealed that selfefficacy, media of consumer education, safety priority, and subjective norm pose a positive and significant relationship with self-protection practices, whereby safety priority was denoted as the most influential predictor for such practices. The findings of this study are highly useful for the government to educate consumers regarding self-protection practices that should be implemented when engaging in online shopping. They should firstly recognise the strategies required to protect themselves against falling victim to rogue online sellers and appreciate that the best form of protection is self-protection.